Cadmium, Copper, Lead, and Zinc Contents of Fish Marketed in NW Mexico - Martín G. Frías-Espericueta; Francia K. G. Zamora-Sarabia; J. Isidro Osuna-López; María D. Muy-Rangel; Werner Rubio-Carrasco; Marisela Aguilar-Juárez; Domenico Voltolina (The Scientific World Journal)
To assess if they were within the safety limits for human consumption, the Cd, Cu, Pb, and Zn contents of fish muscles, bought from separate stalls of the fish markets of nine cities of NW Mexico, were determined by atomic absorption spectrophotometry. Considering all fish and markets, the mean contents were Zn: 23.23±5.83, Cu: 1.72±0.63, Cd: 0.27 ± 0.07, and Pb: 0.09 ± 0.04 µg/g (dry weight). Cu, Zn, and Pb did not reach levels of concern for human consumption, but the high Cd values determined in Mazatlán (Mugil cephalus: 0.48±0.15; Diapterus spp.: 0.57±0.33; Lutjanus spp.: 0.72±0.12; small shark: 0.87±0.19 µg/g dry weight) indicate that this was the only metal of concern for human health because the daily individual consumption of fish muscle to reach the PTDI would be within 0.27 and 0.41 kg.